Effect of obesity and overweight on academic performance among school going adolescents - Sayeejan, P.; Nithlavarnan, A. (The Open University of Sri Lanka, 2020)
Obesity is a problem among school children worldwide. Prevalence of adolescent obesity has increased in recent years in the Jaffna peninsula. Recent studies indicate that obesity affects children’s memory functions and cognitive capabilities. The aim of the study was to find the effect of obesity and being overweight on the academic performance of adolescent girls in the Jaffna Municipal Area. A cross sectional descriptive survey design was used in this study. A total of 761grade ten adolescent girls were selected from four girls’ schools in the Jaffna Municipal Council. The first term marks for six core subjects obtained from overweight and obese students and randomly selected same number of normal weight students, were analyzed using the Minitab18 statistical software using Mann-Whitney U test and two sample t-tests to establish the relationship of academic performance. Perceptions, attitudes and the challenges faced by obese and overweight students were assessed using a questionnaire. The prevalence of overweight and obesity were 17%. The marks of the normal weight students were higher for Science, Tamil language, English language and History. But there was no difference in Mathematics and Religion marks. 80% of students were aware of the impact of obesity. Nearly 68% of obese and overweight students were bullied about their body shape by peers and relations. 64% of the obese and overweight girls suffered with other disease related to obesity. Half of them reported that they were dissatisfied about their body shape and their academic performance. Among the overweight and obese girls, 60% reported that daytime drowsiness affected their learning; 55% had shortage of memory; 10% of them had frequent fatigue. However, they were very sociable and possessed leadership qualities. Furthermore, they had the ability to handle their own problems and challenges with self-confidence. It was also reported that 79% of them engaged in activities to reduce their excess bodyweight. They followed a controlled diet and engaged in physical exercises such as walking, jogging, yoga practices and dancing. The findings of this study provide evidence that the overweight and obesity affect the academic performance of adolescent school going girls and its stresses the need for large-scale preventive strategies that need to be implemented in the Jaffna peninsula.
Keywords: Academic performance; Adolescent girls; Obesity; Overweight; Jaffna Municipal Area